The movement of the trunk and breast during front crawl and breaststroke swimming - Mills, C.; Lomax, M.; Ayres, B.; Scurr, J. (Journal of Sports Sciences, 2015)
Breast displacement has been investigated in various activities to inform bra design, with the goal of minimising movement; however, breast motion during swimming has yet to be considered. The aim was to investigate trunk and breast kinematics whilst wearing varying levels of breast support during two swimming strokes. Six larger-breasted females swam front crawl and breaststroke (in a swimming flume), in three breast support conditions while three video cameras recorded the motion of the trunk and right breast. Trunk and relative breast kinematics were calculated. Greater breast displacement occurred mediolaterally in the swimsuit condition (7.8, s = 1.5 cm) during front crawl and superioinferiorly in the bare-breasted condition (3.7, s = 1.6 cm) during breaststroke, with the sports bra significantly reducing breast displacements. During front crawl, the greatest trunk roll occurred in the sports bra condition (43.1, s = 8.3°) and during breaststroke greater trunk extension occurred in the swimsuit condition (55.4, s = 5.0°); however, no differences were found in trunk kinematics between the three breast support conditions. Results suggest that the swimsuit was ineffective as a means of additional support for larger-breasted women during swimming; incorporating design features of sports bras into swimsuits may improve the breast support provided.